WPP, Ford, and Team Detroit : marketing for global clients - Rosenthal, Jean; Sinha, Arun; Dhar, Ravi ([London] : SAGE, 2016)
In 2006, WPP, the world's largest advertising holding company, merged personnel from five separate agencies to serve Ford, its largest client. 'Team Detroit' represented a sharp departure from WPP's previous client relationships. Agencies within holding companies generally battled for accounts, facing each other in industry bakeoffs or managing separate marketing portfolios. 'Hiving off' personnel from existing agencies to create a bespoke entity had rarely been tried. While pulling together Team Detroit proved to be quite challenging, the new agency meshed well with Ford's streamlined marketing function. Team Detroit was able to produce extremely imaginative campaigns, introducing new groups to Ford products. Ford then asked Team Detroit to coordinate all global marketing. WPP and Team Detroit created 'Blue Hives,' new bespoke agencies for global regions. This case study examines this topic.
Originally Published in: Rosenthal, J., Sinha, A., & Dhar, R. (2013). WPP, Ford, and Team Detroit - Marketing for Global Clients. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://nexus.som.yale.edu/team-detroit.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; WPP (Firm); Ford Motor Company; Marketing -- Case studies; Export marketing -- Case studies